Financial planning among Islamic economics students in Yogyakarta - Putri, Ida Kurnia (Journal of Islamic Economics Lariba, 2016)
This article analyses financial planning for students who studying Islamic economic two universities in Yogyakarta, that is UIN Sunan Kalijaga and Universitas Islam Indonesia. This study is conducted by convenience sampling on 30 samples of each group.Â  The questionnaire is then distributed to collect data related to financial planning, knowledge, and control. The results show that 60 respondents (53% men) generally had low Islamic financial planning. Statistically there is no difference between the two groups of samples. In addition, this study also shows that financial knowledge variables statistically affect the financial planning of the students, while the control variables do not significantly influence it. However, both variables, the variable knowledge and control variables, significantly affect financial planning.